Thực trạng hoạt động giáo dục kĩ năng sống cho học sinh ở các trường tiểu học huyện Khánh Vĩnh, tỉnh Khánh Hòa - Nguyễn , Thị Ngọc Bé; Trần , Đăng Vinh (Tạp chí Giáo dục, 2024)
Life skills education for primary school students plays an important role in the comprehensive development process for each student; however, in reality, life skills education activities for students of this age group still have certain limitations, especially in difficult areas and ethnic minorities. Survey results on life skills education activities for students in secondary schools in Khanh Vinh district, Khanh Hoa province show that the goals, content, form, methods of life skills education and testing, this performance assessment is carried out quite regularly and the results achieved are quite good; conditions serving the implementation of life skills education activities are assessed to be relatively safe and secure. The research results will be the basis for proposing measures to improve the effectiveness of life skills education for students in the area.